The Change of Retinal Sensitivity in Diabetic Retinopathy after Photocoagulation - Arif Budiman, Hartono, Angela Nurini A Angela Nurini Agni (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2009)
Background: Panretinal photocoagulation is used to destroy new blood vessel growth which develops on large areas of retina. Burns that occur would cause scars, that would stop bleeding. Laser has shown benefit in decreasing advance visual loss. Several studies stated that panretinal photocoagulation also decreased the light sensitivity, peripheral visual acuity, and night visual, paracentral scotoma, choroidal neovascularization (rare). submacular fibrosis, and laser injury cycatrical widening, Study on this problem is needed. Objective: To find out the influence of panretinal photocoagulation on retinal sensitivity in diabetic retinopathy patients. Methods: This study used pretest-posttest design. Subjects were diabetic retinopathy patients who visited Ophthalmology Outpatient Clinic Unit Dr. Sardjito Hospital and Dr. Yap Eye Hospital, Yogyakarta from March 2008 to January 2009. All subjects underwent panretinal laser photocoagulation and visual field was examined before treatment and 1 month (4 weeks) after treatment. Data were analyzed descriptively. The difference of retinal sensitivity before and after treatment were analyzed with paired Hest. Result: 19 patients (34 eyes) were included in the study. Average duration of diabetes mellitus in the subjects was 10.44 + 5.26 years. Most (82.4%) subjects had no history of hypertension. The number of laser given to subjects were 826-1850 burns (the average was 1164+218.95). There was improvement in the retinal sensitivity after photocoagulation, although it was statistically insignificant (p > 0.05). There was no significant difference between old and new parameters on visual acuity improvement (p = 0.72 Conclusion: There was no significant change in retinal sensitivity between before and 4 weeks after panretinal photocoagulation in diabetic retinopathy patients. Key words: retinal sensitivity - panretinal photocoagulation - diabetic retinopathy